Neuroscience of Empathy: Bridging Neurophysiology and Organizational Well-being - Abdul Qadeer; Aisha Amin; Ayesha Aziz; Sadaf Aurangzaib; Saira Muzaffar; Rubia Batool; Awais Ur Rahman (Dialogue Social Science Review (DSSR), 2025)
Medical workers are very much prone to stress in the workplace, and the effects of stress always manifest themselves in an individual’s psychological and physiological state, towards the deterioration of his/her performance at work, and consequently, the worsening of attending patients. These include; Empathy, mental health and the disability level because they influence job satisfaction and thus the organizational commitment. The purpose of this study was to investigate the mediational influence on the relationship of neuropsychological measures and organizational wellbeing from five cities of Pakistan. A cross-sectional study design adopted; participants’ empathy levels assessed using the Empathy Quotient (EQ), pain using the Visual Analog Scale (VAS); participants’ disability ratings obtained using the Disability Rating Index (DRI); and their anxiety and depression levels evaluated using the Hospital Anxiety and Depression Scale (HADS) on a sample of 1500 healthcare workers. To test these hypotheses, descriptive and inferential statistics used; ANOVA and correlation tests, mediation analysis based on PROCESS Macro. The correlation coefficients with empathy scores being significantly different from zero in the case of anxiety, depression and disability. Both measured anxiety and assessed depression fully mediated by empathy also found to have direct impact on neuropsychological disability. Variations of these variables also seen cross-cities displaying that there are regional differences of the health of health care workers. The is a need to tackle both the physical and psychological aspects of health care systems so as to improve the current health outcomes of the scientists, doctors, nurses, etc., who in return will deliver better results for the health of the patients’ as well as increase productivity of various health facilities. The mediation analysis also indicates that empathy plays the most crucial role in affecting the mental health and disability status of the respondent.